Euro Area Policies : 2009 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Member Countries. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This 2009 Article IV Consultation focuses on euro area policies. The euro area remains in recession, with signs of improvement yet to evolve into a recovery. The large drop in financial wealth, an associated increase in private savings, tight financing conditions, and the adjustment of global imbalances are key drivers of the economic decline. Executive Directors have welcomed the broad arsenal of macroeconomic policies and financial sector interventions deployed by euro area authorities and Member States to address the crisis.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet